Effects of zinc supplementation on serum copper to zinc and CRP to albumin ratios in hemodialysis patients - Hajji, Marwa (Journal of Medical Biochemistry, 2020)
Background: Zinc (Zn) deficiency is a common condition and could contribute to poor outcomes in hemodialysis patients. The aim of this study was to evaluate effects of Zn supplementation on serum copper (Cu) to Zn and CRP to albumin ratios in HD patients. Methods: Seventy-seven HD patients were enrolled in a multicenter simple-blind randomized clinical trial. Only 37 HD patients completed the study; they were randomly divided into two groups and supplemented with zinc sulfate (n=17) or placebo (n=20) for two months. Serum Zn and Cu were measured by atomic absorption spectrophotometry. Serum albumin and hypersensitive-C-reactive protein were assessed by colorimetric and immunoturbidimetric method, respectively. Determinations were performed before and after the supplementation. Results and conclusions: After two months of supplementation, serum Zn significantly increased and Cu to Zn ratio decreased in Zn supplemented group, but remained unchanged in placebo group. In parallel, serum albumin concentrations significantly increased and CRP to albumin ratio decreased in Zn supplemented group, only.Zn supplementation reduces Cu to Zn and CRP to albumin ratios in HD patients. These changes point towards an improvement in nutritional, oxidative and inflammatory statuses. The study findings suggest that correcting Zn deficiency reduce poor outcomes in HD patients.